ENT 300 : Tasty Cake House / Azri Amizam ... [et al.] - Amizam, Azri; Zailani, Muhammad Amirul; Bi Sakhir, Muhamad Adib; Suhaimi, Mohammad Sarhan (2021)
Tasty Cake House is a pastry shop in Sungai Petani, Kedah, Malaysia. Its main target is to provide its clients with a tasty, high-quality pastry and an outstanding eating experience. The site is in a densely populated residential area, attracting staff is simple because employees can walk to work. Employees must also be cared for in order for them to feel comfortable and protected while working, since this will improve their productivity. Tasty Cake House vision is to serve our customers satisfaction through delicious, high-quality pastry and extraordinary food experience while working towards greater good for our employees, the community and the environment and their mission is to exceeding customer expectations is achieved through dedicated staff and commitment to meeting the new standards. We targeting to bring our customers the ultimate taste of our pastry experience. The meaning of the logo is want to give the customers happiness by experience of the cookies and pastries. The smoke on the top of the cake represents the freshness of the cakes are made where we will serve the pastry fresh from oven. The brown colour is a natural colour that evokes a sense of strength and reliability. Also, the company make a simple logo to make sure the customer clear about the business and also will remember to our logo. There are five top management which is General manager, administrative manager, marketing manager, production manager and financial manager. These 5 top managers play a big role in the company so that the company will continuously being a successful business. The company also provide goods to their employees which is EPF and SOCSO, maturity leave and paternity leave, bonus, annual leave and sick leave.